"Nightmares–Family Medicine" Course Is an Effective Acute Care Teaching Tool for Family Medicine Residents. Issue 3 (June 2019) - Gilic, Filip; Schultz, Karen; Sempowski, Ian; Blagojevic, Ana
Abstract : Introduction: Simulation is an effective method for teaching acute care skills but has not been comprehensively evaluated with family medicine (FM) residents. We developed a comprehensive simulation-based approach for teaching acute care skills to FM residents and assessed it for effectiveness. Method: We compared the effectiveness of our standard acute care simulation training [Acute Care Rounds (ACR)] to a more comprehensive simulation-based acute care program, Nightmares–Family Medicine (NM). We used a self-reported comfort scale as well as video-captured performance on an acute care Objective Structured Clinical Examination (OSCE). Seventy-seven of our FM residents in their postgraduate year 1 between July 2012 and June 2015 participated in the study. Wilcoxon matched pairs and one-tailed t tests analysis was used for analyzing the comfort scale, Whitney-Mann, and χ 2 for the OSCE performance. Results: Nightmares–Family Medicine's initial 2-day session significantly improved the resident's self-assessment scores on all 20 items of the questionnaire ( P < 0.05). Time-matched ACR improved 11 of 20 items ( P < 0.05) level. Follow-up NM sessions improved 5 to 8 of 20 items ( P < 0.05). Follow-up ACR sessions improved 1 to 5 of 20 items ( P < 0.05). The means taken at the end of postgraduate year 1 year were higher for 13 of 20 items in the NM group ( P < 0.05) as compared with ACR group. The NM group scored significantly higher on both the mean scores of OSCE individual categories ( P < 0.01) and the Global Assessment Score ( P < 0.05). Significantly less NM residents failed the OSCE (n = 1/30, 3.3% vs n = 8/37, 21.6%, P < 0.05). Conclusions: "Nightmares–Family Medicine" course is very effective at teaching acute care skills to FM residents and more so than our previous curriculum.